Prevalence of organic central precocious puberty in males: criteria for a high index of suspicion - Maria Elisa Amodeo; Annalisa Deodati; Stefania Pedicelli; Giulia Mirra; Valentina Pampanini; Stefano Cianfarani (Endocrine Connections)
Background: A high prevalence (40–75%) of organic brain lesions in boys with central precocious puberty (CPP) has been reported. Objectives: To evaluate the causes of CPP in a large cohort of males and to identify the possible predictive factors for organic brain lesions in males. Design: An observational study was conducted in 102 otherwise healthy boys with CPP diagnosed from 1998 to 2023 in a single tertiary center. Methods: All boys underwent a thorough clinical, endocrine and neuroimaging assessment with a detailed evaluation of the pituitary region. Results: Organic CPP was found in only 8/102 children (7.8%). Children with brain tumors were younger than 8 years, had no family history positive for precocious puberty and maternal menarche occurred at an age significantly more advanced than in children with idiopathic CPP. Headache was reported at diagnosis in 7/8 children with brain tumors. A progressive increase in the occurrence of idiopathic CPP in males has been observed in the last two decades with a peak of new diagnoses during the pandemic lockdown. Conclusions: Our findings indicate that the prevalence of pathological brain lesions in boys with CPP is considerably lower than previously reported, thus making the diagnosis less alarming. Age younger than 8 years, presence of neurological symptoms, family history negative for precocious puberty in the first-degree relatives and age of maternal menarche older than 11 years raise suspicion of organic CPP and should lead to prompt neuroimaging. Significance statement: Differently from what has been reported in most previous studies, our study has shown a low incidence of brain tumors in male children with precocious puberty, thus making the diagnosis less alarming for parents and physicians. Some criteria for a high index of suspicion of brain tumors in boys with precocious puberty have been identified. Finally, a progressive increase in the occurrence of idiopathic CPP in boys has been observed over the past two decades with a peak of new diagnoses during the pandemic lockdown, as previously reported in girls.